The emblematic species of flora and fauna of the city of Guayaquil and of the province of Guayas, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2015)
A definition and characteristics for emblematic species is provided. Following these, 27 emblematic taxa of the city of Guayaquil and of the province of Guayas, in the coast of Ecuador, are presented here: Fourteen species of vascular plants and 13 species of fauna. The emblematic species of vascular plants for Guayaquil and the province of Guayas are the following: Cordia macrantha (Boraginaceae), Bursera graveolens (Burseraceae), Laguncularia racemosa var. glabriflora (Combretaceae), Pseudosamanea guachapele (Fabaceae), Gustavia angustifolia (Lecythidaceae), Ceiba trichistandra, Gossypium barbadense, Ochroma pyramidale (Malvaceae), Thalia pavonii (Marantaceae), Psidium guayaquilense (Myrtaceae), Nymphaea oxypetala (Nymphaeaceae), Epidendrum bracteolatum, Encyclia angustiloba (Orchidaceae), and Simira ecuadorensis (Rubiaceae). The emblematic species of fauna of Guayaquil and of the province of Guayas are the following: Simosciurus stramineus (Sciuridae), Ara ambiguus subsp. guayaquilensis, Forpus coelestis, Psittacara erythrogenys (Psittacidae), Myrmia micrura (Trochilidae), Crocodylus acutus (Crocodylidae), Mastigodryas reticulatus (Colubridae), Coniophanes dromiciformis (Dipsadidae), Trilepida guayaquilensis (Leptotyphlopidae), Iguana iguana (Iguanidae), Ceratophrys stolzmanni (Ceratophryidae), Porphyrobaphe iostoma (Orthalicidae), and Eulaema polychroma (Apidae).